Memórias do Centro Pan-Americano de Febre Aftosa – Opas/Oms: Uma contribuição para a história da saúde pública veterinária das Américas - BERSOT, Dayse Carias (2014)
This dissertation presents the history and memories of the Pan American Center for foot-andmouth disease PANAFTOSA – PAHO/WHO, an international body of the Pan American Health Organization and World Health Organization, which is located in the city of Duque de Caxias – Rio de Janeiro and it works on the premises of an old farm in the neighborhood of São Bento. The institution has a collection of documents depicting the history, the memories of individuals who by their passed, the evolution and the scientific discoveries of an era that were of paramount importance to the areas of public health and Veterinary Public Health not only of Brazil as to the countries that make up the region of the Americas, in addition to being an institution of international reference with respect to research and action on the diseases of animal origin that may affect society. The proposal of this study consists in boost reflections on relations between history and memory, in addition to presenting the historical trajectory of the institution, with a view to bringing the light of public knowledge a little of the history of PANAFTOSA - PAHO/WHO. This research has a qualitative character, of bibliographic and documentary stamp and this inserted into the search line representation of Historicity, memory and Speech, interdisciplinary master's degree program in arts and Humanities. For the development of this work we use as sources, a part of the historical documents belonging to the institution. The documentation found in the archives of the Pan American Center for foot-and-mouth disease in assisted in the writing of this dissertation and later was the basis for the description of the historical trajectory of Panaftosa - PAHO/WHO. As the documents found are administrative character and mostly are closed to public access, we chose to perform a search in the historical collection of the national library in search of records about the emergence and Panaftosa related events. Carried out the searches found some journalistic material, published by the press of the then national capital, the city of Rio de Janeiro, which featured in their reports about the institution matters. Before the material found brief analysis performed with the intention of checking what the newspapers of the time were talking about the institution since its creation in 1950 until 1962 (last record found carrying news about Panaftosa).